Elective cesarean section versus induced vaginal delivery: Do any differences in terms of neonatal respiratory morbidities exist? Elective cesarean section versus induced vaginal delivery - Özdoğar, Mahli Batuhan; Ayar, Murat; Hamitoğlu, Şerif; Olukman, Özgür (Journal of Surgery and Medicine, 2023)
Background/Aim: Transient tachypnea of the newborn (TTN) is mostly a benign and self-limiting common physiological disorder. Certain factors, such as elective cesarean section (CS) not preceded by spontaneous labor, delivery before 39 gestational weeks, and perinatal asphyxia, interfere with the fetal–neonatal transition. In our study, we aimed to review the results of hospitalized newborns who receive a diagnosis of TTN and investigate the possible relationship between the implementation of labor induction and the occurrence of this disorder. Methods: This study used a case-control study design. We scanned the hospital records of 156 term newborns hospitalized between January 2017 and January 2018 who received a diagnosis of TTN and who did not have any additional fetal and/or maternal risk factors. Demographic features, mode of delivery, and implementation of labor induction in vaginal deliveries were recorded and compared to the data from 150 healthy term infants. Infants were then split into two groups according to their type of labor induction, and a separate subgroup analysis was performed in terms of the risk of TTN development. Results: The incidence of TTN was 2.9% in vaginal deliveries and 8.5% in CSs. Differences between groups regarding gestational age, birth weights, gender, elective induction in vaginal deliveries, interventions in the delivery room, and types of intervention were found (P<0.05). The risk of developing TTN was 2.5 times higher in the induction group compared to those who did not receive induction but still developed TTN (P<0.001). Also, the risk was significantly higher in the induction group compared to those who did not receive induction and did not develop TTN (P<0.001). After applying a logistic regression analysis, labor induction (odds ratio: 1.005; 95% confidence interval: 1.003–1.008, P<0.001) was found to be an independent signiﬁcant risk factor for developing TTN. Conclusions: This study indicates that infants born via electively induced vaginal delivery had significantly higher rates of TTN. Therefore, elective labor induction can be added as a new risk factor for TTN development. In our opinion, labor induction without valid medical and obstetric indications should be avoided due to maternal and fetal complications.